PERANCANGAN UI/UX PADA APLIKASI BERBASIS MOBILE E-TICKET MUSEUM DI JAKARTA DENGAN MENGGUNAKAN METODE DESIGN THINKING - Dhian Sweetania; Achmad Hafidz (Jurnal Teknik dan Science, 2023)
Currently, the public's interest in visiting museums in Jakarta can be channeled through an E-Ticket-based application. This E-Ticket-based application enables the public to easily purchase tickets and gain general knowledge about museums in Jakarta. This application serves as an initial exploration stage that assists the public in pursuing their interests. The design of this application utilizes the design thinking method, which consists of the empathize, define, ideate, prototype, and usability testing stages. Consequently, this design provides a recommendation in the form of a UI/UX model for the mobile application, showcasing information and E-tickets for museums in Jakarta. The design model of this E-ticket-based mobile application is based on the high interest of the public in visiting museums in Jakarta. This application plays a role in channeling the public's satisfaction with museums in Jakarta.